2010
DOI: 10.1007/s10878-010-9332-8
|View full text |Cite
|
Sign up to set email alerts
|

SIRALINA: efficient two-steps heuristic for storage optimisation in single period task scheduling

Abstract: Abstract. In this paper, we study the general problem of one-dimensional periodic task scheduling under storage requirement, irrespective of machine constraints. We have already presented in (Touati and Eisenbeis, 2004) a theoretical framework that allows an optimal optimisation of periodic storage requirement in a cyclic schedule. Since our optimization problem is NP-hard (Touati, 2002), solving an exact integer linear programming formulation is too expensive in practice. In this article, we propose an effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Now the problem that must be solved by SIRA is to compute a valid reuse graph with minimal er ∈E reuse,t μ t (e r ), without increasing the initiation interval II if possible. Also, instead of minimising the register requirement, SIRA may simply look for a solution such that er ∈E reuse,t μ t (e r ) ≤ R t , where R t is the number of available registers of type t. We may propose many exact method models (the problem has been proved NP-complete in [22]) or heuristics based on the SIRA framework [8,21].…”
Section: Periodic Register Constraintsmentioning
confidence: 99%
See 4 more Smart Citations
“…Now the problem that must be solved by SIRA is to compute a valid reuse graph with minimal er ∈E reuse,t μ t (e r ), without increasing the initiation interval II if possible. Also, instead of minimising the register requirement, SIRA may simply look for a solution such that er ∈E reuse,t μ t (e r ) ≤ R t , where R t is the number of available registers of type t. We may propose many exact method models (the problem has been proved NP-complete in [22]) or heuristics based on the SIRA framework [8,21].…”
Section: Periodic Register Constraintsmentioning
confidence: 99%
“…There are many heuristics and methods that may be used. SIRALINA [8,21] is our most powerful method, we have already demonstrated that it a really efficient heuristic for SIRA: it considers an initial DDG with multiple register types, and produces an associated DDG to bound or to minimise the register requirement before SWP. SIRALINA is a two steps heuristic, with an algorithmic complexity equal to O( V 3 log V ), where V is a notation for the cardinality of a set.…”
Section: Application To the Sira Framworkmentioning
confidence: 99%
See 3 more Smart Citations